2023
DOI: 10.6007/ijarbss/v13-i2/16337
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Website Disclosures for Sustainability Reporting of Islamic Religious Institutions

Abstract: Public sector organizations play an essential role in supporting the government's commitment to sustainable development. These organizations are expected to disclose more social and environmental information than private companies due to public contracts. Malaysian State Islamic Religious Councils (SIRCs) is one of the government agencies responsible for distributing and disseminating adequate and accurate information to various stakeholders, especially the public. These SIRCs frequently organize sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For instance, Al Sayed et al (2021) used a cointegration analysis to show that the fiscal policy in Egypt was sustainable from 1990/ 1991 to 2017/2018. Similarly, Abdullah et al (2012) found a cointegration between fiscal sustainability indicators and GDP in Malaysia, indicating fiscal sustainability. The results of our study offer valuable insights into the impact of different factors on economic growth in Egypt, which can inform policymaking and future research.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, Al Sayed et al (2021) used a cointegration analysis to show that the fiscal policy in Egypt was sustainable from 1990/ 1991 to 2017/2018. Similarly, Abdullah et al (2012) found a cointegration between fiscal sustainability indicators and GDP in Malaysia, indicating fiscal sustainability. The results of our study offer valuable insights into the impact of different factors on economic growth in Egypt, which can inform policymaking and future research.…”
Section: Discussionmentioning
confidence: 86%
“…The results also showed that inflation was affected by shocks of fiscal sustainability, particularly the negative shocks from 1977 to 1986, which ended with hyperinflation in 1985. In Abdullah et al (2012) study, the authors employed Vector Autoregression (VAR) analysis to demonstrate how policy changes can be examined within a VAR framework. Additionally, they utilized multivariate cointegration to determine the relationship between fiscal sustainability and GDP indicators.…”
Section: Empirical Overviewmentioning
confidence: 99%